Experimental and theoretical investigations on moulded wooden tubes made of beech (Fagus sylvatica L.). (15th November 2016) - Hartig, Jens U.; Wehsener, Jörg; Haller, Peer
Highlights: The wood moulding technique transverse to the grain was applied to beech. Wooden tubes of structural size were produced in an industrial facility. Tubes of beech have a load-bearing capacity under axial compression of 60 N/mm 2 . The tubes fail by compressive failure parallel to grain – not by transverse splitting. FRP working as confinement on the outer surface of the tubes improves ductility. Abstract: Wood moulding is a novel technique for producing structural elements of solid wood by plastic forming. The technique is applied to beech ( Fagus sylvatica L.) to produce relatively thin walled, hollow profiles of structural size for building purposes. The principles of wood moulding are presented by analytical equations and results of experimental investigations on densification and compression set recovery. The load-bearing behaviour of tubes of structural size under axial compression is shown. Moreover, the effect of glass-fibre reinforced plastics as confinement was investigated. The experiments revealed a load-bearing capacity of the unreinforced tubes under axial compression of about 60 N/mm 2 .